Z dziejów profesjonalizacji. Seminaria nauczycielskie w Prusach Południowych (1793-1806) i seminarium Sulechowskie = From the times of professionalisation. Teaching colleges in South Prussia (1793-1806) and the college in Sulechow - Łukasiewicz, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The process of professionalisation consisted in involving another occupations by school preparation. It concerned also the teaching profession. Some teachers had university preparation in the Middle Ages and from the 16th century Jesuits teaching colleges were present. However, the overwhelming majority of teachers in lower schools did not have professional preparation. A greater impact on changes in this range was pul in the Enlightenment period and the process was more advanced in Prussia than in the Republic of Poland.
Keywords: Prusy Południowe; edukacja i pedagogika; seminarium nauczycielskie; Sulechów (woj. lubuskie) - Królewskie Pedagogium; historia - 18-19 w.